Peranan Kepala Sekolah Dalam Meningkatkan Mutu Pendidikan Di Sekolah - Fairuz Dhiya Putri; Nadila Sahla Mulia; Selvy Gita Cahyani (International Forum of Researchers and Lecturers, 2023)
School is an educational institution that has the goal of educating the nation's successors and producing quality output. In achieving these goals, schools need an organizational structure that can carry out its functions properly. The principal plays a key role as a driving force in improving the quality of education in schools, where schools are considered as educational organizations. This article will discuss the role of the principal in improving the quality of education in schools, namely the role of the principal in management in schools, the role of the principal as a key in creating a good organizational structure, and the role of the principal as an agent of change and role model in the world of education. The research method used in this article is literature study which is supported by various sources, both in the form of previously published books and national journals.